(untitled) (Journal of Plant Disease Sciences, 2020)
Fusarium solani reduces the quality, yield and market value of gladiolus. The pathogen is soil borne in nature, hence difficult to control. Cultivation of resistant varieties is the effective and cheaper method to combat as compared to chemical control. Hence twenty five varieties and thirty five hybrid lines were screened in artificial sick soil under natural field condition against wilt disease. Out of twenty five gladiolus varieties only one variety IIHR-77-59-32 was free from wilt disease while 22 varieties showed moderately resistant reaction along with two (Psitacinus hybrid and Sancerre) exhibit susceptible reaction to Fusarium wilt. Among the thirty five gladiolus hybrids, two hybrids viz. 07-7 and 07-23 were free from wilt disease and remaining hybrid showed moderately resistant reaction.